144x-54=18(8x-3)

Simple and best practice solution for 144x-54=18(8x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 144x-54=18(8x-3) equation:


Simplifying
144x + -54 = 18(8x + -3)

Reorder the terms:
-54 + 144x = 18(8x + -3)

Reorder the terms:
-54 + 144x = 18(-3 + 8x)
-54 + 144x = (-3 * 18 + 8x * 18)
-54 + 144x = (-54 + 144x)

Add '54' to each side of the equation.
-54 + 54 + 144x = -54 + 54 + 144x

Combine like terms: -54 + 54 = 0
0 + 144x = -54 + 54 + 144x
144x = -54 + 54 + 144x

Combine like terms: -54 + 54 = 0
144x = 0 + 144x
144x = 144x

Add '-144x' to each side of the equation.
144x + -144x = 144x + -144x

Combine like terms: 144x + -144x = 0
0 = 144x + -144x

Combine like terms: 144x + -144x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4x-6x+21=5x+35 | | 4x-10+9+6x=34 | | x+1=3+x | | -8d+1=-3 | | 4(x-6)=-3x-17 | | 4x+8-7x+2=5x-8x+7 | | 24x-4+3=24x+12-10 | | 5-3n=10 | | 3x=12x^2 | | 80-k=41 | | 3x-4y=16*x | | 2x^2+4x-4=-6 | | 6(4b-2c)+9f= | | 5y^2-40y^2=0 | | 10(t-4)+4t=7(2t-5)-9 | | 6x+4=6x-9 | | 3x-6+4x-3=180 | | 6+7n=41 | | 2(2r+3)=10r | | 3ax-4x= | | 45+.02x=50+.3x | | 25x^2+y^2-100x-125=0 | | -9x^2-2x+4=8 | | 2X-3=20x | | 6(5-3y)=84 | | 5x+50y=16 | | 20.50x+150=903 | | 30x+9=24+14x | | 4x-2(x-2)=-3+4x-1 | | 4(x-6)=-3-7 | | 2x-14y-20=0 | | 2.3x+4.8=9 |

Equations solver categories